Geologic significance and optimization technique of sweet spots in unconventional shale systems. (July 2019) - Zou, Caineng; Yang, Zhi; Zhu, Rukai; Wu, Songtao; Fu, Jinhua; Lei, Dewen; Hou, Lianhua; Lin, Senhu; Pan, Songqi
Graphical abstract: Tight oil and shale oil are the important unconventional resources in shale systems, in which the tight oil is the most realistic and profitable resources. Due to special geological environments, lacustrine tight oil is different from marine tight oil in North America. Sweet-spotting is critical to develop these abundant resources, in which three aspects including geology, engineering and economy have been taken into consideration. In this paper, we proposed the definition of sweet spot zone and sweet spot interval in shale system, and discuss the geological significance & related technologies. Tight oil and shale oil should be assessed as a whole system during the future geological evaluation and technology development. The productivity of tight oil and shale oil will be increased by 30–50 million tons, making the economic development of oil in continental shale systems in China. Highlights: The world-level lacustrine tight oil accumulations in China. Geological aspects of tight oil in shale systems. Critical evaluation and development technologies for sweet spotting. Abstract: Crude oil in unconventional shale systems, present as tight oil and shale oil, accumulates inside an oil kitchen in formations with coexistent sources and reservoirs. Organic matter present in oil shale is not yet mature and requires heating to convert it into crude oil. Oil exploration in shale systems involves the exploration of shale oil retained in source rocks and tight oil rich zones located near source rocks. Tight oil is a type of realistic unconventional oil resources in China. The marked increase in potential shale oil reserves, and exploration of these reserves, will result in a shale oil revolution similar to that experienced for shale gas. Based on a systematic comparison of geologic features of shale systems in the US and China, the geologic significance of the sweet spots in shale systems is proposed. This zone contains an abundance of unconventional oil in shale systems that can be explored and developed under current economic and technical conditions. The sweet spot zone refers to the zone in the tight oil rich zone which has industrial value within the scope of matured high-quality source rocks on the plane. The sweet spot interval refers to the high-productivity interval of tight oil which has industrial value through artificial stimulation. The main aim of oil exploration in shale formations is to identify the sweet spots. The distribution of the economic sweet spots in shale systems is evaluated by overlapping the geologic, engineering and economic sweet spots. Resource assessment techniques, the identification of logging data properties, high-resolution 3D seismic surveys, horizontal well production from well pads, and artificial reservoir development of sweet spots in oil-bearing shale formations can assist efficient development of oil. Globally, shale formations contain a significant volume of oil reserves. Currently, stimulated reservoir volume (SRV) techniques in horizontal wells in marine shale gas formations in the United States have average peak-productivity cycles of 10–15 years. To achieve commecial oil production in lacustrine shale systems in China, it is important to utilize large formation thicknesses and the high abundance of organic matter. In addition, the development of practical and economic techniques will result in an increase of productivity of tight oil and shale oil by 30–50 million tons, as well as the economic development of oil in lacustrine shale systems in China.